Unravelling the Intricacies of Auto Brewery Syndrome and its Microbial Dynamics: A Narrative Review - Bhagyesh Sapkale; Shreya Singh; Dhruba Chandi (Journal of Clinical and Diagnostic Research, 2025)
Auto Brewery Syndrome (ABS), often referred to as Gut Fermentation Syndrome (GFS), is a sporadic disorder characterised by the internal production of alcohol, leading to symptoms that resemble alcohol intoxication, including vertigo, slurred speech and confusion. The article explores uncommon presentations of ABS, such as an oral version and a new variation in which endogenous fermentation within the urinary system results in the production of ethanol. One of the main causes of ABS is thought to be a fungal dysbiosis of the gut, which occurs due to an overabundance of yeast. The pathophysiology of ABS is associated with the mycobiome, a component of the gut microbiota that ferments certain carbohydrates into ethanol, mimicking food allergies or intolerances. Using a comprehensive search strategy that includes the PubMed, Science Direct and Google Scholar databases, this review investigates ABS with a focus on recent research published in the last 10 years. The involvement of gut bacteria is emphasised, particularly the abnormal development that results in endogenous alcohol synthesis. Microbiological strains associated with ABS, including high alcohol-producing variant of Klebsiella pneumoniae (HiAlc KPN) and Candida albicans, are examined. The article discusses the challenges associated with diagnosing ABS, including the use of breath analysers, clearance rates and variations in endogenous ethanol production among different ethnic groups. Furthermore, medicolegal issues are addressed, such as the use of ABS as a defence in drunk driving cases. In conclusion, ABS illuminates the intricate relationship between the human body and its microbiota, highlighting the potential consequences of microbial imbalance.